The impacto of enviromental marketing campaigns: the four sheres model : El modelo de las cuatro esferas - Romeo Delgado, Marina; Yepes i Baldó, Montserrat; Berger, Rita; Vidal Moranta, Bartomeu (Folios, revista de la Facultad de Comunicaciones y Filología, 2011)
This article shows the results of an exploratory study conducted in the town of Badalona (Barcelona,Spain) following the implementation of the waste disposal Law Law ( DOGC,Law 1/2009,July, 21st). This Law, recently passed by the catalan government, aims to promote citizens participation in organic waste separation disposal. Specifically, the general objective of this research is to analyze attitudes and behavior in the separation and disposal of organic waste in order to establish guiedelines and suggestions for improvement in designing enviromental marketing campaigns, and their assessment.